Dual-functional Ti(IV)-IMAC material enables simultaneous enrichment and separation of diverse glycopeptides and phosphopeptides - Huang, Junfeng (Anal Chem, 2021)
Simultaneous enrichment and fractionation of diverse proteins/peptides possessing different post-translational modifications (PTMs) from the same biological samples is highly desirable to reduce sample consumption, avoid complicated sample processing, and enable studies of potential crosstalks between different PTMs. In this work, we report a new approach to enable the simultaneous enrichment and separation of glycopeptides, phosphopeptides and mannose-6-phosphate (M6P) glycopeptides by using dual-functional Ti(IV)-IMAC material. Moreover, we also made the separation of neutral and sialyl glycopeptides, mono- and multi-phosphopeptides possible by performing different elution according to the differences in their electrostatic or hydrophilic properties. These separations are effective and efficient to eliminate the signal suppression from neutral glycopeptides for sialyl glycopeptide detection, allowing separation of mono-phosphopeptides from multi-phosphopeptides, as well as detection of M6P glycopeptides that are free from the above-mentioned modifications. This new strategy significantly improves the coverage and identification numbers of glycopeptides, phosphopeptides and M6P glycopeptides by 1.9, 2.3, and 4.3-fold compared with the conventional method, respectively. This is the first report on simultaneous enrichment and separation of neutral and sialyl glycopeptides, mono- and multi-phosphopeptides and M6P glycopeptides via dual-functional Ti(IV)- IMAC, revealing novel insights into potential crosstalk among these important PTMs.